Peran Orang Tua dalam Menanamkan Pembiasaan Mencuci Tangan pada Anak Usia 4-5 Tahun di BKB PAUD Kelurahan Utan Kayu Utara - Elissanti, Evi (Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to obtain data regarding the role of parents in implementing the habit of hand washing in children 4-5 years old at BKB PAUD Utan Kayu Utara Subdistrict, Jakarta. This research uses a quantitative descriptive method with a survey method. This research was conducted by distributing questionnaires to respondents. The sample in this study were parents of students aged 4-5 years at BKB PAUD, Utan Kayu Utara Subdistrict. The technique used in determining the sample in this research is cluster sampling. The results of this study show that the role of parents in implementing the habit of hand washing in children aged 4-5 years is in the high category with 88% of the respondents. It can be concluded that parents are aware of the importance of getting their children to washing their hands. Parents are the first educators for children. The role of parents towards children is as caregivers, mentors, educators and as role models in shaping the child's character. In this case, parents are role models in getting children used to washing their hands so that their hands are clean and protected from disease.